The effect of cytomegalovirus on clinical and paraclinical as well as immune parameters of children with rotavirus infection - M. Yu. Sliepchenko; S. V. Kuznetsov (Zaporozhye State Medical University, 2021)
The aim is to evaluate the effect of cytomegalovirus on clinical and paraclinical as well as immunological parameters in children with rotavirus infection (RVI). Materials and methods. 50 children aged one to three years, patients with moderate and severe intestinal infections of rotavirus etiology were examined. All children were examined for herpes virus infections types 1, 2, 4, 5, 6. Enzyme-linked immunosorbent assay (ELISA) was used to determine the level of specific Ig G and Ig M for herpes viruses types 1, 2, 4, 5, 6, and in the case of a positive test, polymerase chain reaction (PCR) determined the presence of DNA (qualitatively) of these herpesviruses. Group 1 (mono-RVI), which was taken as a reference, included 33 children in whom no infection with any of these viruses of the herpes group was detected. Group 2 included 17 patients who underwent RVI on the background of CMV infection, the presence of infection with other viruses of the herpes group was excluded. Immune response parameters (CD 3+, CD 4+, CD 8+, CD 16+, CD 22+, Ig A, Ig M, Ig G, IL 1β, 4, TNF-α) in the acute period of the disease and in the period of convalescence were analyzed. Qualitative indicators were given in the form of absolute and relative (%) value. Significance of differences was determined using Pearson's χ2 test (Pearson's Chi-squared test). Quantitative indicators were given in the form of median (Me) and values of lower (LQ) and upper (UQ) quartiles. The significance of differences in quantitative indicators in two unrelated groups was determined using the Mann-Whitney U-test. The threshold value of the confidence level was taken as 0.05. Results. The analysis of the obtained data allows to establish that in the acute period of RVI infection in children with CMV leads to lower figures of temperature reaction, lower vomiting rate, prolongation of hospitalization, along with decrease in leukocytes, CD 16+ (%) cells and immunoregulatory index (CD 4+/CD 8+) against the background of increased levels of monocytes, CD 8+ (%) T-lymphocytes, concentrations of IL-4 and TNF-α. During convalescence, the presence of CMV is associated with an increase in the duration of fever and diarrhea, an increase in monocytes, CD 8+ (%) T cells, concentrations of IL-4, TNF-α and lower figures of immunoregulatory index, CD 16+ (%), CD 22+ (%) T cells and Ig M. Conclusions. Latent cytomegalovirus infection in children with rotavirus gastroenteritis significantly affects a number of clinical and paraclinical as well as immune parameters, which leads to a decrease in the intensity of clinical manifestations in the acute period of the disease and the prolongation of some symptoms during convalescence.